Managing Organizational Diversity : Trends and Challenges in Management and Engineering - Machado, Carolina, 1965-; Davim, J. Paulo (Springer, 2017)
This book provides a comprehensive overview of organizational diversity management, intended to help readers implement effective strategies and maximize the value of organizational diversity. Written by experts from a range of disciplines, it presents cutting-edge research and best practices in this field. Further, it addresses the challenges that organizations face in order to successfully manage organizational diversity and presents the application of theoretical concepts. Individual chapters explore topics including workforce diversity, knowledge management, innovation and change, and decision-making. Providing an invaluable resource for students and researchers in the fields of human resource management, industrial engineering and international business, the book will also benefit human resource managers, engineers and economists.
Keywords: Diversification in industry.; Branches (Business enterprises); Corporations -- Subsidies.; Organization.; elektronické knihy; electronic books